Sociodemographic, academic, and lifestyle factors associated with anxiety and depression among Medical students (Research, Society and Development, 2025)
The objective of this study was to investigate the prevalence of anxiety and depression symptoms and to analyze the association between sociodemographic, academic, and lifestyle factors and these outcomes among medical students at an institution in the interior of Bahia, Brazil. This was an observational, cross-sectional, quantitative survey conducted with 110 students who completed the GAD-7 and PHQ-9 instruments, in addition to a characterization questionnaire. Descriptive analyses, bivariate tests, and multivariate logistic regression were performed to identify independent predictors of anxiety and depression. The results indicated high prevalences of anxiety (53.6 percent) and depression (58.2 percent). In the adjusted analysis, age showed an inverse association with anxiety, indicating that younger students had a higher likelihood of experiencing anxious symptoms. For depression, female sex remained an independent predictor, with a higher probability of depressive symptoms compared with males. Variables such as leisure activities, physical activity, sufficient income, and course satisfaction did not retain significance after multivariate adjustment. These findings suggest that psychological distress among medical students is substantial and influenced by individual and sociodemographic factors. The identification of more vulnerable groups, such as women and younger students, underscores the need for institutional policies promoting mental health and continuous preventive interventions. Longitudinal studies are recommended to deepen the understanding of these determinants and guide more effective support strategies.